2021
DOI: 10.1093/ageing/afab006
|View full text |Cite
|
Sign up to set email alerts
|

A classification tree to assist with routine scoring of the Clinical Frailty Scale

Abstract: Background the Clinical Frailty Scale (CFS) was originally developed to summarise a Comprehensive Geriatric Assessment and yield a care plan. Especially since COVID-19, the CFS is being used widely by health care professionals without training in frailty care as a resource allocation tool and for care rationing. CFS scoring by inexperienced raters might not always reflect expert judgement. For these raters, we developed a new classification tree to assist with routine CFS scoring. Here, we te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
84
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 27 publications
3
84
0
3
Order By: Relevance
“…The CFS was operationalised at waves 1-5 of TILDA according to the published CFS Decision Tree 24 . Six items were used in the decision tree to distinguish between CFS classes as follows: (i) number of basic activities of daily living requiring help (BADL); (ii) number of instrumental activities of daily living requiring help (IADL); (iii) number of chronic conditions (28 chronic and cardiovascular conditions shown in Table 1 ); (iv) self-rated health – excellent, very good, good, fair or poor; (v) one item from the Center for Epidemiological Studies Depression scale: during the past week how often have you felt that everything that you did was an effort – rarely or none of the time, some or a little of the time, occasionally or a moderate amount of time, all of the time; and (vi) moderate or vigorous activity on ≥1 days in the past week as assessed using the International Physical Activity Questionnaire Short Form (IPAQ-SF) 26 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The CFS was operationalised at waves 1-5 of TILDA according to the published CFS Decision Tree 24 . Six items were used in the decision tree to distinguish between CFS classes as follows: (i) number of basic activities of daily living requiring help (BADL); (ii) number of instrumental activities of daily living requiring help (IADL); (iii) number of chronic conditions (28 chronic and cardiovascular conditions shown in Table 1 ); (iv) self-rated health – excellent, very good, good, fair or poor; (v) one item from the Center for Epidemiological Studies Depression scale: during the past week how often have you felt that everything that you did was an effort – rarely or none of the time, some or a little of the time, occasionally or a moderate amount of time, all of the time; and (vi) moderate or vigorous activity on ≥1 days in the past week as assessed using the International Physical Activity Questionnaire Short Form (IPAQ-SF) 26 .…”
Section: Methodsmentioning
confidence: 99%
“…Despite the rolling out of dedicated training modules for more accurate CFS scoring 22 , 23 , a criticism of the CFS has been the possible subjectivity in the scoring, bringing the possible danger of lack of scoring consistency between individuals and across agencies. However, to address those concerns, the authors of the CFS have published a classification tree method to assist with routine scoring of the CFS 24 . This also allows the retrospective implementation of the CFS in a dataset when the required CFS decision tree variables have been collected.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we advocate for the use of mRFI as a screening tool for frailty since it has been externally validated in prior studies [2], we agree that it should be used in conjunction with other tools to obtain an integral preoperative assessment. To our knowledge, the Rockwood clinical frailty scale that is cited by the author has not been externally validated in the preoperative setting to this date, and its diagnostic performance is known to give inaccurate scores when applied by providers with limited experience in frailty care [3,4]. Interestingly, a recently published multicenter prospective observational study by Pugh et al demonstrated good levels of agreement while using this scale; however, factors that independently associated with higher ratings were also detected, indicating that personal bias existed [5].…”
Section: Dear Editormentioning
confidence: 99%